A generalization of the Valanis model for friction modelling. (1st November 2022) - Jalali, Hassan; Jamia, Nidhal; Friswell, Michael I.; Haddad Khodaparast, Hamed; Taghipour, Javad
Abstract: The complex dynamics of a frictional contact interface have been the subject of many research investigations. However, a comprehensive model has not been proposed that can be easily solved and considers the effect of all parameters of interest, i.e., the variation in contact pressure, the interaction of normal and tangential direction mechanisms, and contact surface degradation. This paper proposes a generalized slip model based on the original Valanis model with the ability to generate non-symmetric hysteresis loops for frictional contact interface modelling and identification. Various numerical and simulation results are used to show the capability of the generalized Valanis model. The advantages of the model presented in this paper are its simplicity and accuracy. The model offers an explicit solution for the Hysteresis loop and is Lipschitz continuous, making it an ideal choice for real-time analyses, such as in digital twins' applications. The model can represent both point-to-point contacts in a joint interface and the joint interface as a whole. The latter application is considered in this paper.